DESIGNING DIGITAL TEACHING MATERIALS FOR TEACHERS AT ELEMENTARY SCHOOL LEVEL - Fitri Senny Hapsari; Miftahul Farid Mochamad Ahyar; Ayi Ahmad Maulana Yusup (STKIP PGRI Sumatera Barat, 2022)
This public service is intended to help partners at SDN Ratu Jaya 2 Depok increase teachers and students digital literacy. that is a part of a larger movement to make available educational resources designed specifically for use with online education. An approach known as